A comparison of intact and reconstituted samples of a silt tailings. Issue 2 (25th February 2022) - Reid, David; Fanni, Riccardo
Abstract : The critical state approach, based heavily on the use of the moist tamping (MT) reconstitution method, is finding increasing application in tailings engineering practice. However, the available studies comparing the behaviour of intact and reconstituted samples of silt tailings have indicated significant discrepancies. This paper outlines a comparison of triaxial tests carried out on samples of tailings trimmed intact from high-quality blocks and reconstituted using both MT and slurry deposition (SD) methods. Particular focus was placed on the potential for layering within the intact block samples, which indicated that while they were relatively uniform, some minor layering was present – an aspect that has not been considered in detail in previous similar studies. The SD samples tended towards, but did not reach, the critical state line (CSL) identified with MT specimens. Intact block samples generally tended towards the MT CSL, contrary to most previous comparisons. However, greater scatter was apparent in the intact block sample end states than those of the MT specimens, which is hypothesised to result from layering seen in the block samples. A direct comparison of the shearing behaviour of MT and intact block samples from the same void ratio and stresses was inconclusive owing to the inherent variation in intact block sample behaviour.